Collaborative Governance in Local Governments: Yogyakarta Special Regional Fund - Imansyah Imansyah; Lisa Sophia Yuliantini; Titin Purwaningsih (Universitas Muhammadiyah Tangerang, 2024)
This study investigates the collaborative governance strategies employed by the Special Region of Yogyakarta (DIY) in leveraging its special regional funds to advance regional development and address local needs. Focusing on the cooperation between the regional government, local government units (LGUs), non-governmental organizations (NGOs), and community groups, the research utilizes a qualitative descriptive approach and data analysis with NVivo 12 Plus. Findings reveal that collaborative governance in DIY is primarily driven by LGUs, which contribute to the partnership with an intensity of 72%, while NGOs and community involvement are comparatively limited at 13%. The research underscores the high engagement level of local government units in utilizing DIYâ€™s special funds to enhance service quality, promote economic empowerment, and support education and community welfare. Despite these efforts, the study highlights a critical need to balance collaboration intensity across sectors, ensuring that private sector and community contributions are effectively integrated into the governance framework. By doing so, the equitable distribution and sustainable impact of DIY's special funds can be maximized, promoting broader socio-economic benefits across the region. This research contributes to the growing body of knowledge on collaborative governance by highlighting the importance of inclusive multi-actor engagement for regional resource utilization and effective governance outcomes.Â Penelitian ini mengkaji strategi tata kelola kolaboratif yang diterapkan oleh Daerah Istimewa Yogyakarta (DIY) dalam memanfaatkan dana istimewa untuk mendukung pembangunan daerah dan memenuhi kebutuhan lokal. Fokus penelitian ini adalah pada kerja sama antara pemerintah daerah, satuan kerja perangkat daerah (SKPD), organisasi non-pemerintah (LSM), dan kelompok masyarakat, dengan pendekatan deskriptif kualitatif serta analisis data menggunakan NVivo 12 Plus. Temuan menunjukkan bahwa tata kelola kolaboratif di DIY didominasi oleh peran SKPD dengan intensitas kontribusi sebesar 72%, sedangkan keterlibatan LSM dan masyarakat masih relatif rendah, yaitu 13%. Penelitian ini menyoroti tingginya tingkat keterlibatan SKPD dalam pemanfaatan dana istimewa DIY untuk meningkatkan kualitas layanan, pemberdayaan ekonomi, pendidikan, dan kesejahteraan masyarakat. Meski demikian, penelitian ini juga menekankan perlunya keseimbangan dalam intensitas kolaborasi lintas sektor agar kontribusi sektor swasta dan komunitas dapat terintegrasi secara efektif dalam kerangka tata kelola. Dengan demikian, distribusi manfaat dan dampak dana istimewa DIY dapat dimaksimalkan secara merata, mendorong manfaat sosial-ekonomi yang lebih luas di seluruh wilayah. Penelitian ini memberikan kontribusi pada literatur tata kelola kolaboratif dengan menunjukkan pentingnya keterlibatan multi-aktor yang inklusif untuk pemanfaatan sumber daya daerah dan hasil tata kelola yang efektif.Â